2021
DOI: 10.1021/acs.jmedchem.1c01335
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic BODIPY-Appended Half-Sandwich Iridium(III) Complex Forms Protein Adducts and Induces ER Stress

Abstract: Half-sandwich complexes of iridium­(III) are currently being developed as anticancer drug candidates. In this context, we introduce IrBDP for which the C^N chelating phenyloxazoline ligand carries a fluorescent and lipophilic BODIPY reporter group, designed for intracellular tracking and hydrophobic compartment tropism. High-resolution analysis of cells cultured with IrBDP showed that it quickly permeates the plasma membrane and accumulates in the mitochondria and endoplasmic reticulum (ER), generating ER stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The distribution of complex 6 inside the cells was investigated next. DNA ,, as well as the mitochondria, ,,,,,,, endoplasmic reticulum (ER), , or lysosomes , have been described to be targets of iridium cyclometalated complexes. The cells were incubated with the complex at 10 μM for 4 h at 37 °C to allow its maximum accumulation and the major cellular compartments (nuclear, membrane/particulate, cytosolic, and cytoskeletal) were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of complex 6 inside the cells was investigated next. DNA ,, as well as the mitochondria, ,,,,,,, endoplasmic reticulum (ER), , or lysosomes , have been described to be targets of iridium cyclometalated complexes. The cells were incubated with the complex at 10 μM for 4 h at 37 °C to allow its maximum accumulation and the major cellular compartments (nuclear, membrane/particulate, cytosolic, and cytoskeletal) were isolated.…”
Section: Resultsmentioning
confidence: 99%
“…He et al introduced triphenylamine (TPA) and its derivatives into half-sandwich Ir III complexes, which endowed them with suitable fluorescence properties . These studies confirmed that the introduction of fluorescent molecules (rhodamine B, coumarin, triphenylamine, BODIPY, etc.) could endow half-sandwich Ir III complexes with suitable fluorescence through proper design; however, there have been few reports of complexes with excellent fluorescence properties and antitumor activity.…”
Section: Introductionmentioning
confidence: 89%
“…Metallodrugs are emerging as alternative ER stress inducers. , Compared to organic drugs, they offer additional metal-centered reactivity for drug design including coordination chemistry, photo­(redox) chemistry, and dark redox chemistry. The metallodrugs can trigger the ER stress via four distinct upstream events. , First, coordinatively unsaturated complexes (CUCs) form metal–biomolecule bonds, e.g., Pt 2+ in cisplatin binds N7 of purine residues in DNA, Au + complexes coordinate a selenocysteine residue in thioredoxin reductase, Ir 3+ half-sandwich complexes bind histidine and cysteine residues in proteins, and a Ru 3+ complex BOLD-100/KP1339 binds ribosomal proteins . Second, redox-active complexes induce the catalytic generation of reactive products via electron transfer either to or from intracellular substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in normal cells containing the low level of UPs, this equilibrium is shifted toward the unbound UPs, which can be normally processed. Thus, the optimized BUP will be toxic to cancer cells, but not affect normal cells (Figure B), thereby solving the problem of side effects of common ER stress inducers. …”
Section: Introductionmentioning
confidence: 99%